Assessing Heavy Metals Contamination in Suspended Particulate Matter in Jakarta Bay, Indonesia - Fitri Budiyanto; Lestari Lestari (BULLETIN OF THE MARINE GEOLOGY, 2019)
Suspended Particulate Matter (SPM) is an important compartment within water column due to its capability in adsorbing pollutant like heavy metals. However, there was limited information regarding SPM and its heavy metals content in Jakarta Bay. Therefore, this study was proposed to understand the spatial distribution, source and to assess metal content in SPM in Jakarta Bay. The samples were collected from 24 stations in April 2011 and were then analyzed using acid digestion processes adopted from USEPA 3050b. The generated data were then modeled to determine the spatial distribution of metals in SPM. The result revealed that the concentration of Cd, Cu, Ni, Pb and Zn in SPM were as follow: 10-110; 21-472; 14-356; 7-107; 87-4255 mg.kg-1, respectively. Since Cd, Pb and Zn in SPM were majorly concentrated in the area closed to harboring activities, the activities was suspected in contributing of high input of those metals, meanwhile, Cu and Ni was mostly came from riverine runoff. The computation of Index of Geoaccumulation (Igeo) revealed that the major area in Jakarta Bay was unpolluted by Cu, Pb, Zn, and Ni in SPM however 96% of the selected area were strongly contaminated by Cd in SPM. Thus, this study emphasized that harbor area as a dominant source of metals in SPM in Jakarta Bay and required to be well managed.Keywords: Jakarta Bay, Suspended Particulate Matter, heavy metals, contamination.Materi Partikulat Tersuspensi (SPM) merupakan bagian penting dalam kolom air karena kemampuannya dalam menjerat polutan seperti logam berat. Akan tetapi, informasi mengenai SPM dan kandungan logam berat dalam SPM di Teluk Jakarta terbatas. Oleh karena itu, tujuan dari studi ini adalah untuk mengetahui distribusi spasial, dan sumber logam berat serta menilai kualitas lingkungan berdasar kandungan logam berat dalam SPM di Teluk Jakarta. Sampel SPM diambil dari 24 titik observasi pada bulan April 2011 kemudian dianalisis dengan proses digestif asam yang diadopsi dari USEPA 3050b. Data yang didapat kemudian dimodelkan untuk mengetahui distribusi spasial logam berat dalam SPM. Hasil analisis menunjukkan bahwa konsentrasi Cd, Cu, Ni, Pb dan Zn dalam SPM secara berurutan sebagai berikut: 10-110; 21-472; 14-356; 7-107; 87-4255 mg.kg-1. Cd, Pb dan Zn lebih ditengarai bersumber dari aktivitas pelabuhan karena konsentrasi Cd, Pb dan Zn di area tersebut tinggi sementara Cu dan Ni lebih banyak berasal dari limpasan sungai. Perhitungan Indeks Geoakumulasi (Igeo) menunjukkan bahwa sebagian besar area tidak tercemar oleh Cu, Pb, Zn dan Ni akan tetapi 96% area teramati tercemar Cd. Oleh karena itu, studi ini menyarankan untuk ditingkatkannya manajemen pembuangan limbah di pelabuhan sebagai sumber logam.Kata kunci: Teluk Jakarta, Materi Partikulat Tersuspensi, logam berat, pencemaran.